The Effects of Wellness In The Schools (WITS) on Physical Activity During Recess in New York City Public Schools - Priya Khorana (Physical Activity and Health, 2019)
Only 21% of U.S. children meet federal physical activity (PA) guidelines. Schools have insufficient time for physical education classes. School children typically have recess daily, making recess a venue to increase PA. Programs such as Wellness In the Schools (WITS) provide a coach during school recess to lead organized activities and encourage all students to participate may provide students with health, psychological, academic and social benefits. This study was a quasi-experimental matched-control design with seven WITS intervention schools and seven matched control schools, measuring two outcomes: 1) PA level, 2) PA type (measured with an observational tool: System for Observing Play and Leisure Activities in Youth (SOPLAY)). Outcomes were measured in second and third graders pre-(T0) and post-(T1), one school-year into the WITS intervention during outdoor (T0 and T1) and indoor (inclement weather) (T1 only) recess. Results at T1 were compared between control and WITS schools with ANOVA tests. For PA level, the WITS intervention increased PA in indoor recess, a higher percentage of WITS girls and boys were vigorously active, a lower percentage were sedentary, and overall recess PA levels were higher (all p ≤ .001). For PA type, WITS intervention schools had higher overall PA level during ball-like activities during outdoor recess in girls (p = 0.002) and boys (p = 0.010). This study suggests active recess interventions increase PA level during indoor recess and during ball-like activities in outdoor recess, suggesting the WITS intervention has the potential to increase PA during school and help students receive the benefits of regular PA.